KARMA YOGA DALAM KEPEMIMPINAN ORGANISASI - Wididana, Gede Ngurah (Institut Hindu Dharma Negeri Denpasar, 2018)
Leadership determines the success of an organization in achieving organizational goals. Karma yoga is a service attitude practiced by everyone as a leader for himself and organization to provide the best service to others and organization. The application of karma yoga as the service attitude of life taught in the Bhagavad Gita is really important to be studied relevant to the leadership of organization in modern era. The servant leadership described by Greenleaf is closely related to karma yoga as a service attitude by leader in organization, which aims to serve sincerely by dedicating service to god. Karma yoga is depicted in Mahabharata as a patient and loving attitude, courageus and responsible, diligent and learner, honest and loyal. Karma yoga constitutes the basic for the servant leadership to realize organizational goals.